Characterisation of tetanus monoclonal antibodies as a first step towards the development of an in vitro vaccine potency immunoassay. (June 2021) - Riches-Duit, Rebecca; Hassall, Laura; Kogelman, Amy; Westdijk, Janny; Rajagopal, Shalini; Davletov, Bazbek; Doran, Ciara; Dobly, Alexandre; Francotte, Antoine; Stickings, Paul
Abstract: Batch release testing for human and veterinary tetanus vaccines still relies heavily on methods that involve animals, particularly for potency testing. The quantity and quality of tetanus antigen present in these products is of utmost importance for product safety and clinical effect. Immunochemical methods that measure consistency of antigen content and quality, potentially as an indicator of potency, could be a better choice and negate the need for an in vivo potency test. These immunochemical methods require at least one well characterised monoclonal antibody (mAb) that is specific for the target antigen. In this paper we report the results of the comprehensive characterisation of a panel of mAbs against tetanus with a view to select antibodies that can be used for development of an in vitro potency immunoassay. We have assessed binding of the antibodies to native antigen (toxin), detoxified antigen (toxoid), adsorbed antigen and heat-altered antigen. Antibody function was determined using an in-house cell-based neutralisation assay to support prior in vivo potency data that was available for some, but not all, of the antibodies. In addition, antibody affinity was measured, and epitope competition analysis was performed to identify pairs of antibodies that could be deployed in a sandwich immunoassay format. Not all characterisation tests provided evidence of "superiority" of one mAb over another, but together the results from all characterisation studies allowed for selection of an antibody pair to be taken forward to assay development.